Poverty, food insecurity, and the behavior for childhood internalizing and externalizing disorders - Slopen, Natalie; Fitzmaurice, Garrett; Williams, David R; Gilman, Stephen E (Journal of the American Academy of Child and Adolescent Psychiatry, 2010)
This study investigated the associations of poverty and food insecurity over a 2-year period with internalizing and externalizing problems in a large, community-based sample. A total of 2,810 children were interviewed between ages 4 and 14 years at baseline, and between ages 5 and 16 years at follow-up. Primary caregivers reported on household income, food insecurity, and were administered the Child Behavior Checklist, from which we derived indicators of clinically significant internalizing and externalizing problems. Prevalence ratios for the associations of poverty and food insecurity with behavior problems were estimated. At baseline, internalizing and externalizing problems were significantly more prevalent among children who lived in poor households than in nonpoor households, and among children who lived in food insecure households than in food-secure households. In adjusted analyses, children from homes that were persistently food insecure were 1.47 (95% CI = 1.12 to 1.94) times more likely to have internalizing problems and 2.01 (95% CI = 1.21 to 3.35) times more likely to have externalizing problems compared with children from households that were never food insecure. Children from homes that moved from food secure to insecure were 1.78 (95% CI = 1.07 to 2.94) times more likely to have externalizing problems at follow-up. Persistent food insecurity is associated with internalizing and externalizing problems, even after adjusting for sustained poverty and other potential confounders. These results implicate food insecurity as a novel risk factor for child mental well-being; if causal, this represents an important factor in the etiology of child psychopathology, and potentially a new avenue for prevention.